Guidelines for Developing Tourism Potential of Ban Salangpun Community, Salangpun Sub-District, Lamplaimat District, Buriram Province - Promchat, Ramate (Academic MCU Buriram Journal, 2021)
The purposes of this study were 1) to study the potential of Ban Salangpun community, Salangpun sub district, Lamplaimat district, Buriram province, and 2) to search for guidelines of developing tourism potential of this community. The researcher collected the data through In-dept Interview, Focus Group, Walk-in Survey, and Participatory Observation. The results revealed that Salangpun community has 3 tourism potentials: 1) community cultures, 2) local goods and food, and 3) tourist attractions. 1) The Potential of Community Cultures: The ancient people of this community were Thai-Chinese races. They settled there and their culture was the identity of the community. 2) The Potential of Local Goods and Food: The community’s signature goods and food for the tourists were cantaloupe and: Larb Peking Duck, Panang local Chicken, Tom Klong, Organic Eggplant Soup, etc. They were important highlight in attracting tourists. 3) Lastly, Potential of Tourist Attractions: Salangpun train station, Saiyud market, Sangjun learning center, and an ancient 100 years old - Thai-Chinese barn, etc. All those places have had history and relation of community culture since the past time. These history and cultures become 3 guidelines for developing the tourism potential of this community: 1) guidelines for developing community tourism through guide training, 2) guidelines for developing public relation potential, and 3) guideline for building partners in community tourism management.